2016
DOI: 10.3390/app7010013
|View full text |Cite
|
Sign up to set email alerts
|

Passivity-Based Control for a Micro Air Vehicle Using Unit Quaternions

Abstract: Abstract:In this paper the development and practical implementation of a Passivity-Based Control (PBC) algorithm to stabilize an Unmanned Aerial Vehicle (UAV) described with unit quaternions are presented. First, a mathematical model based on Euler-Lagrange formulation using a logarithmic mapping in the quaternion space is introduced. Then, a new methodology: a quaternion-passivity-based control is derived, which does not compute excessive and complex Partial Differential Equations (PDEs) for synthesizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Remark 3: The quaternion-based PD controller (31) is only used to show the effectiveness of the proposed FE system. The study of the controller is out of the scope of this work, more details could be found in [35].…”
Section: A Nominal Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 3: The quaternion-based PD controller (31) is only used to show the effectiveness of the proposed FE system. The study of the controller is out of the scope of this work, more details could be found in [35].…”
Section: A Nominal Controllermentioning
confidence: 99%
“…. Then, from (35) it is clear that fault isolation can be done by analyzing the sign value of the components ofη r , as it is shown in Table 3. Finally, FA control law (33) using (34) can be applied.…”
Section: Fa Control Lawmentioning
confidence: 99%
“…However, it is limited to tracking of the attitude, only. In [25], the idea of a quaternion-passivity-based control is used without the need to solve partial differential equations (PDEs).…”
Section: Introductionmentioning
confidence: 99%
“…The present work uses the model structure exposed in [6,12,15] as a starting point but, as a novel contribution, introduces a nonlinear time-varying mathematic model of the rotors used in the DJI F-450 quadrotor (Figure 1), that is used to perform a more detailed and realistic analysis of the control system through numerical simulations. Several methods have been published to control the fly of SUAV [1,2,5,[9][10][11]13,14,[28][29][30][31][32][33][34][35]. In the present work, we propose a control law structure based on a combination of PID and LQR/LQG algorithms but, in contrast to those exposed in others works [5,[30][31][32][33][34][35], a modified LQR/LQG controller is used to obtain the optimal pre-tuning parameters of four PID controllers, commonly employed for attitude and altitude control in multirotor systems (hover maneuver).…”
Section: Introductionmentioning
confidence: 99%